Emotion Regulation, the Function of Stress Hormones & Digital Technologies - Bravou, Vasiliki; Driga, Anna Maria Stella; Drigas, Athanasios (Technium BioChemMed, 2022)
Emotion control in stressful situations is an important aspect of mental health. On the other hand, acute stress, affects the prefrontal cortex control, probably resulting in a loss of emotion regulation abilities. To lessen the threat, the stress response activates a number of defensive systems, including hormone messenger communication. In this article we are going to examine the present literature in relation to emotion control via understanding the function of the primary stress hormone, cortisol, and that of the catecholamines, epinephrine and norepinephrine. We have also presented and underlined the role of ICTs, web and mobile applications, AI & STEM tools, serious games, e-learning, tele-education services, etc., in the support and improvement procedures for achieving emotional self-control and regulation of the stress hormones.